Non-invasive Metabolomic Profiling of Embryo Culture Medium Using Raman Spectroscopy With Deep Learning Model Predicts the Blastocyst Development Potential of Embryos - Zheng, Wei; Zhang, Shuoping; Gu, Yifan; Gong, Fei; Kong, Lingyin; Lu, Guangxiu; Lin, Ge; Liang, Bo; Hu, Liang (Frontiers in Physiology, 2021)
Purpose This study aimed to establish a noninvasive predicting model via Raman spectroscopy for evaluating the blastocyst development potential of day 3 high-quality cleavage stage embryos. Methods Raman spectroscopy was used to detect the metabolic spectrum of spent day 3 (D3) embryo culture medium, and a classification model based on deep learning was established to differentiate between embryos that could develop into blastocysts (blastula) and that could not (non-blastula). The full-spectrum data for 80 blastula and 48 non-blastula samples with known blastocyst development potential from 34 patients were collected for this study. Results The accuracy of the predicting method was 73.53% and the main different Raman shifts between blastula and non-blastula groups were 863.5 cm-1, 959.5 cm-1, 1008 cm-1, 1104 cm-1, 1200 cm-1, 1360 cm-1, 1408 cm-1, and 1632 cm-1 from 80 blastula and 48 non-blastula samples by the linear discriminant method. Conclusions This study demonstrated that the developing potential of D3 cleavage stage embryos to the blastocyst stage could be predicted with spent D3 embryo culture medium using Raman spectroscopy with deep learning classification models, and the overall accuracy reached at 73.53%. In the Raman spectroscopy, ribose vibration specific to RNA were found, indicating that the difference between the blastula and non-blastula samples could be due to materials that have similar structure with RNA. This result could be used as a guide for biomarker development of embryo quality assessment in the future.